Dermato-cosmeceutical properties of Pseudobombax ellipticum (Kunth) Dugand: Chemical profiling, in vitro and in silico studies - Eman Fikry; Ismail Mahdi; Ahmet Buğra Ortaakarsu; Nora Tawfeek; Melvin Adhiambo Ochieng; Widad Ben Bakrim; Mohamed AO Abdelfattah; Khaled W. Omari; Mona F. Mahmoud; Mansour Sobeh (Elsevier, 2023)
Plant extracts and their individual components have been used to manage skin aging for several decades. Recently, the discovery of new natural bioactive agents, that not only enhance the skin health but also offer protection against various deleterious factors, such as free radicals, ultraviolet radiation, and microbial infections, has been a potential target by many researchers. The aim of the current work was to investigate the phytochemical profile of an ethanol bark extract from Pseudobombax ellipticum, and to evaluate its antioxidant, antiaging and antibacterial activities in vitro. Molecular docking and molecular dynamics studies were adopted to estimate and confirm the binding affinity of several compounds and explain their binding pattern at the binding sites of four target enzymes associated with skin aging, namely collagenase, elastase, tyrosinase, and hyaluronidase. HPLC-MS/MS analysis led to the tentative identification of 35 compounds comprising phenolic acids, and their glycosides, procyanidins and flavonoid glycosides. The extract demonstrated a promising in vitro antioxidant activity in the DPPH and FRAP assays (IC50 56.45 and 15.34 μg/mL, respectively), and was able to inhibit the aforementioned key enzymes with comparable results to the reference drugs. In addition, the extract (6.25 mg/mL) inhibited the biofilm production of Pseudomonas aeruginosa and diminished the swimming and swarming motilities. The docked compounds revealed appreciable binding energy with the tested enzymes and were stable throughout the molecular dynamic simulations. In view of this data, P. ellipticum bark can be regarded as a good candidate for prospective application in derma-cosmeceutical preparations.